PERBAIKAN KEKUATAN DAN DAKTILITAS BALOK BETON BERTULANG MENGGUNAKAN GLASS FIBER REINFORCED POLYMER (GFRP) STRIPS - ', Parmo; ', Taufikkurrahman (SISTEM Jurnal Ilmu Ilmu Teknik, 2014)
Wheres Indonesia is a highly active tectonic zone that is prone to earthquakes. Important issue following the earthquake was retrofit structures to improvement strength and ductility structure. With the advancement of technology today has developed new innovations such as the use of material GFRP (Glass Fiber Reinforced Polymer) for external confinement structure. From the results obtained by the experimental of load capacity increased by 20% for C-2 (retrofit beam with GFRP strengthened 1 layer) compared B-1 (original beam).   Retrofit beam with GFRP is added ductility as shown by the increase in displacement ductility 4% each for B-1 and B-2.